Legality of Artificial Intelligence (AI) Technology in Public Service Transformation: Possibilities and Challenges - Mariyam, Siti; Setiyowati, Setiyowati (APPTHI, 2021)
The purpose of this study is to analyze and formulate transformation policies in public services based on the use of information technology in the 5.0 era. This research is normative juridical research, with the empirical, case, and conceptual approaches, secondary data-based data sources analyzed by descriptive analysis. The results of the study show that the use of technology in the 5.0 era is relevant is Artificial Intelligence (AI) technology; this technology can be used in the context of public services in the cash transfer sector and also in services in the security sector, in the public service sector in the context of providing cash assistance. AI technology is used to process and analyze beneficiary data, and in the security sector, AI technology can be used to predict crime and recommend the presence of security forces. AI can also be used to detect faces where AI can guarantee greater accuracy than humans in face and time police officers. The use of AI in the context of public services has had an impact, namely in the form of a reduction in the role of humans in public services, in addition to placing AI at the forefront of public services, making public service interactions no longer person to person but the person to machine. The challenge of using AI in the public service sector is the very minimal readiness to operationalize the use of AI by the government. Abstrak Tujuan dari penelitian ini adalah menganalisis dan merumuskan kebijakan transformasi dalam pelayanan publik berbasis pemanfaatan teknologi informasi di era 5.0. Penelitian ini merupakan penelitian yuridis normatif, dengan pendekatan empiris, kasus dan konseptual, berdasarkan sumber data sekunder yang dianalisis dengan metode analisis deskriptif. Hasil kajian menunjukkan bahwa pemanfaatan teknologi di era 5.0 yang relevan adalah teknologi Artificial Intelligence (AI), teknologi ini dapat digunakan dalam konteks pelayanan publik di bidang transfer tunai dan juga dalam pelayanan di bidang keamanan. , di bidang pelayanan publik dalam rangka pemberian bantuan tunai. Teknologi AI digunakan untuk mengolah dan menganalisis data penerima manfaat dan pada bidang keamanan teknologi AI dapat digunakan untuk memprediksi kejahatan dan merekomendasikan keberadaan aparat keamanan selain AI juga dapat digunakan untuk mendeteksi wajah dimana AI dapat menjamin akurasi yang lebih besar dari manusia dalam menghadapi dan petugas polisi waktu. penggunaan AI dalam konteks pelayanan publik telah memberikan dampak yaitu berupa pengurangan peran manusia dalam pelayanan publik, selain menempatkan AI sebagai garda terdepan dalam pelayanan publik, membuat interaksi pelayanan publik tidak lagi bersifat personal. ke orang tetapi orang ke mesin. tantangan penggunaan AI di sektor pelayanan publik adalah kesiapan yang sangat minim untuk mengoperasionalkan penggunaan AI oleh pemerintah. Kata kunci: Kecerdasan buatan, Pelayanan public, Penggunaan Teknologi Informasi